Egypt's ICT Reform: Adoption Decisions and Perspectives of Secondary School Teachers During COVID-19 - Alaa Badran; Lamiaa Eid; Hanan Abozaied; Noha Nagy (SAGE Publishing, 2021)
This descriptive quantitative survey study explored the perspectives of 221 secondary school teachers from 19 Egyptian governorates on the ICT (information and communications technology) component of the 2017 education reform. Data were collected during the novel context and mandates dictated by the widespread COVID-19. The main indicators of teachers' perspectives were adopted from Rogers's diffusion of innovation theory, while their digital competencies were aligned with the levels of the UNESCO ICT Competency Framework. The study found that the majority of participants hold positive perspectives on the relative advantage of ICT integration, average perspectives on its complexity, and negative perspectives on its compatibility with Egypt's education needs and main priorities. Findings further highlight the presence of multiple challenges that may affect teachers' decision to adopt/reject the ICT reform, including the human and technological infrastructures as well as communication. The insights gained from this study may assist in understanding teachers' level of persuasion, possible sources of social resistance, and need for effective capacity building.